Perception of house owners in Kuching: A case study for low cost houses and high end houses - Kon, Alice (Universiti Malaysia Sarawak, (UNIMAS), 2012)
Housing provision for all in any country is very crucial in order to ensure social- economic stability and to promote national development. This study focuses on the perception of the current house owners of low cost, medium cost & high end houses in Kuching city, Sarawak.) The need to examine and identify the perceptions of house buyers towards the houses which they bought will shed light on what a house buyer looks for when deciding to purchase a house. For this purpose, the study will look into the intended improvements which are lacking in a house and which also are wanted by house owners.